K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

6 tháng 8 2022

loading...  

6 tháng 8 2022

\(x-\left(\dfrac{1}{3}+\dfrac{1}{5}-\dfrac{1}{7}\right)=\dfrac{1}{7}-\dfrac{1}{3}\)

\(\Leftrightarrow x-\dfrac{1}{3}-\dfrac{1}{5}+\dfrac{1}{7}=\dfrac{1}{7}-\dfrac{1}{3}\)

\(\Leftrightarrow x=\dfrac{1}{7}-\dfrac{1}{3}-\dfrac{1}{7}+\dfrac{1}{3}+\dfrac{1}{5}\)

 x\(=\dfrac{1}{5}\)

\(x-\left(\dfrac{1}{3}+\dfrac{1}{5}-\dfrac{1}{7}\right)=\dfrac{1}{7}-\dfrac{1}{3}\)

\(\Rightarrow x-\dfrac{41}{105}=-\dfrac{4}{21}\)

\(\Rightarrow x=-\dfrac{4}{21}+\dfrac{41}{105}\)

\(\Rightarrow x=\dfrac{1}{5}\)

(0,5)2+2x=(0,7)2

=>0,25+2x=0,49

=>2x=0,49-0,25

=>2x=0,24

=>x=0,24:2

=>x=0,12

Vậy x=0,12

(0,5)2 + 2 . x = (0,7)2

0,25 + 2 . x = 0,49

2 . x = 0,49 - 0,25

2 . x = 0,24

x = 0,24 : 2

x = 0,12

\(\left|2y-5\right|=0\\ \Rightarrow2y-5=0\\ \Rightarrow2y=5\\ \Rightarrow y=\dfrac{5}{2}\)

\(\dfrac{15^{21}.27^8.49^{29}}{21^{45}.25^{10}.7^{15}}\\ =\dfrac{\left(3.5\right)^{21}.\left(3^3\right)^8.\left(7^2\right)^{29}}{\left(3.7\right)^{45}.\left(5^2\right)^{10}.7^{15}}\\ =\dfrac{3^{21}.5^{21}.3^{24}.7^{58}}{3^{45}.7^{45}.5^{20}.7^{15}}\\ =\dfrac{3^{45}.5^{21}.7^{58}}{3^{45}.7^{60}.5^{20}}\\ =\dfrac{5}{7^2}\\ =\dfrac{5}{49}\)